Risk Management Model for SMEs: A Story from Pandemic - Kurniawan, Putu Sukma (Universitas Gorontalo, 2023)
This study aims to develop a risk management model (RMM) that can be used by the small and medium enterprises (SMEs) to survive in a pandemic condition. An approach with psychological theory was used in the context of developing the RMM. The research method is based onqualitative paradigm and there are three stages in this study to develop the RMM for SMEs in a pandemic condition. This study finds that there are several problems and challenges that the SMEs management have to deal with the pandemic condition. Additional explanations are prepared to create the connection between the RMM with the Kubler-Ross Grief Cycle Theory. This RMM can be used by the SMEs management as a guide for carrying out an organization's business activities in a pandemic.Â